Analysis of falls in patients with epilepsy enrolled in the perampanel phase III randomized double‐blind studies. (21st November 2016) - Leppik, Ilo E.; Yang, Haichen; Williams, Betsy; Zhou, Sharon; Fain, Randi; Patten, Anna; Bibbiani, Francesco; Laurenza, Antonio
Summary: Objective: To analyze occurrence of falls among patients with partial seizures, with/without secondarily generalized seizures (SGS), and primary generalized tonic–clonic seizures (PGTCS) in the perampanel phase III clinical studies. Methods: Studies 304, 305, and 306 randomized subjects (≥12 years) with drug‐resistant partial seizures (with/without SGS) to perampanel 2, 4, 8, or 12 mg or placebo for double‐blind treatment. The adverse event (AE) of falls was analyzed in the Safety Analysis Set (N = 1480). Study 332 randomized subjects aged ≥12 years with a diagnosis of PGTCS into perampanel 8 mg or placebo groups for double‐blind treatment. In a systematic review of reported falls in the study 332 Safety Analysis Set (N = 163), falls were queried to establish whether each was seizure related; subjects with falls resulting from a seizure were not included in this analysis. Results: For studies 304/305/306, treatment‐emergent falls occurred in 5.1% perampanel‐treated versus 3.4% placebo‐treated subjects with partial seizures. Exposure‐adjusted rate for falls (falls/subject‐month of exposure) was greater for total perampanel than for placebo (0.0175 vs. 0.0093) and was dose related for those receiving perampanel. In subjects with SGS, incidence of treatment‐emergent falls was 4.3% in perampanel and 4.0% in placebo groups. Exposure‐adjusted rates were 0.0169 and 0.0097 falls per subject‐month of exposure in perampanel and placebo, respectively. For study 332, 2.5% perampanel‐treated and 1.2% placebo‐treated subjects with PGTCS had treatment‐emergent falls that were not part of a seizure. Exposure‐adjusted rates were 0.0169 and 0.0032 falls per subject‐month of exposure in perampanel and placebo, respectively. Significance: Results of the perampanel studies suggest that patients with epilepsy should be monitored due to the common risk of falls.